2017
DOI: 10.3389/fpsyg.2016.02055
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Religious Chanting Modulates the Late-Stage Brain Response to Fear- and Stress-Provoking Pictures

Abstract: Chanting and praying are among the most popular religious activities, which are said to be able to alleviate people’s negative emotions. However, the neural mechanisms underlying this mental exercise and its temporal course have hardly been investigated. Here, we used event-related potentials (ERPs) to explore the effects of chanting the name of a Buddha (Amitābha) on the brain’s response to viewing negative pictures that were fear- and stress-provoking. We recorded and analyzed electroencephalography (EEG) da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 56 publications
(57 reference statements)
2
15
1
Order By: Relevance
“…These patterns are particularly noticeable when participants are confronted with fearful events of negative valence. This finding is in line with a previous ERP study, which showed significant differences between RC and NRC during emotion regulation (Gao et al, 2017). The major involvement of subcortical regions, including the amygdala, para-hippocampus, and brainstem (pons) illustrate that RC can influence the function of these emotion-related brain regions in a direct manner.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These patterns are particularly noticeable when participants are confronted with fearful events of negative valence. This finding is in line with a previous ERP study, which showed significant differences between RC and NRC during emotion regulation (Gao et al, 2017). The major involvement of subcortical regions, including the amygdala, para-hippocampus, and brainstem (pons) illustrate that RC can influence the function of these emotion-related brain regions in a direct manner.…”
Section: Discussionsupporting
confidence: 92%
“…The fMRI experiment on emotion regulation followed a previous ERP experiment (Gao et al, 2017). It had a 2 × 3 factorial design with two factors (emotion and chanting), featuring two levels for emotion (neutral and fear) and three levels for chanting (religious chanting, non-religious chanting and no chanting).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…LPP is a broad positive component sensitive to the motivational relevance of visual stimuli (Cuthbert, Schupp, Bradley, Birbaumer, & Lang, 2000;Schupp, Junghofer, Weike, & Hamm, 2004;Schupp et al, 2000). The previous studies Gao et al, 2017;Moser et al, 2009;Zhang et al, 2012Zhang et al, , 2013 suggested that the central-parietal and parietal LPP in general was associated with emotional significance of stimuli, the more positive parietal LPP indicating the enhancement in emotional intensity and the more negative parietal LPP indicating the decrease in emotional intensity. However, several recent studies found higher frontal LPP under reappraisal relative to the viewing condition and argued that enhanced frontal LPP may index increased cognitive effort associated with reappraisal (Bernat, Cadwallader, Seo, Vizueta, & Patrick, 2011;Moser, Hartwig, Moran, Jendrusina, & Kross, 2014;Shafir, Schwartz, Blechert, & Sheppes, 2015).…”
Section: Introductionmentioning
confidence: 99%